Merits of Different Ventricular Lead Locations on Left Ventricular Myocardial Strain and Dyssynchrony in Patients with Cardiac Resynchronization Therapy - Algazzar, Alaa S; Elbably, Mohamed M; Katta, Azza A; Elmeligy, Neama; Elrabbat, Khaled; Qutub, Mohammed A (Cardiology, 2020)
The idea behind cardiac resynchronization therapy (CRT) is to pace both ventricles resulting in a synchronized electro-mechanical coupling of the left ventricle (LV), meaning every effort should be made to improve the percentage of CRT responders. This study aimed at demonstrating the short-term effect of right ventricular apical (RVA) and mid-septal (RVS) lead locations combined with different LV lead positions on LV myocardial strain, dyssynchrony, and clinical outcomes. We examined 60 patients with indication for CRT before and after 6 months of implantation for clinical outcome and CRT response (6-min walk test [6MWT], NYHA class, decrease in left ventricular end systolic volume [LVESV] by >15%), dyssynchrony, and myocardial strain. After 6 months of follow-up, the two RV lead locations represented a significant improvement in 6MWT, left ventricular ejection fraction, and LVESV in comparison to baseline values, but no significant difference was found between both groups. With regards to NYHA class improvement, p values were insignificant between the groups (0.44 and 0.88) at baseline and 6 months after implantation, respectively. The mean 6MWT was 273.8 m in the RVA group compared to 279.0 m in the RVS group (p = 0.84) at baseline. After 6 months of CRT implantation, the 6MWT mean was 326.5 m in the RVA group compared to 316.2 m in the RVS group (p = 0.74). The posterolateral cardiac vein site showed a significant improvement when combined with RVS location in interventricular and intraventricular dyssynchrony, global longitudinal strain, global circumferential strain, and apical circumferential strain (p = 0.01 0.032, 0.02, 0.005, and 0.049), respectively. RVS is not inferior and provides a good alternative to RVA pacing in short-term follow-up. However, the QRS duration, myocardial strain, and dyssynchrony varies depending on RV and LV stimulation sites. Long-term morbidity and mortality outcomes according to LV lead location in coronary sinus need more assessment.